Hubungan Iklim dengan Kejadian Demam Berdarah Dengue (DBD) - Irma Irma; Yusuf Sabilu; Harleli Harleli; Swaidatul Masluhiya AF (Jurnal Kesehatan, 2021)
Dengue Hemorrhagic Fever (DHF) is a serious health problem, especially in tropical countries including east Indonesia. DHF cases in Bau-Bau City in the last three years have shown a significant increasing trend. In 2017 the IR DHF in Bau-Bau was 62,6 per 100.000 population, in 2018 the IR rate was 67,4 per 100,000 population, and the CFR rate was 1%, and in 2019 the IR DHF was 94,9 per 100,000 population with the CFR increasing to 1,3%. The purpose of this study was to determine the relationship between rainfall and humidity with the incidence of DHF. This study is an ecological study using secondary data on DHF and climate which were collected retrospectively. Data on dengue fever for 566 cases were taken from the Health Office of Bau-Bau City and data on climate were taken from the Meteorology, Climatology and Geophysics Agency (BMKG) Meteorological Station Class II Betoambari Bau-Bau City. The analysis was carried out univariate and bivariate with the Spearman correlation test at 0,05 to determine the relationship between rainfall and humidity with the incidence of DHF. The results of the Spearman correlation test of rainfall with the incidence of DHF obtained a value of=0,006 and r=0,35 and air temperature with the incidence of DHF with a value of=0,000 and a value of r=0,576. Climatic factors, namely rainfall and air temperature, are associated with the incidence of dengue fever in Bau-Bau City, Southeast Sulawesi.